On the role of EU cohesion policy for climate policy - Lars P. Feld; Joshua Hassib (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Cohesion policy in the European Union (EU) has been widely accepted as a tool to advance the catch-up process, i.e., helping member countries with lower GDP per capita to grow faster economically in order to arrive at similarly high-income levels as member countries with higher GDP per capita. However, empirical studies provide contradicting evidence as to the success of structural funds in this regard. From a political economics perspective, EU structural funds and their instruments of cohesion policy, but also EU agricultural policy, are interpreted as providing for a compensation for poorer member countries' agreement on additional steps of European integration. In recent times, climate policy has entered the cohesion strategy of the EU as higher energy costs due to carbon pricing may require programs for transformation of the existing carbon intensive capital stock to a carbon-neutral capital stock. Structural funds should thus help countries in the transformation process to carbon neutrality such that they do not fall behind. An example is Next Generation EU (NGEU) that is aiming at member countries' transition to carbon neutrality. In this paper, the goals of EU cohesion policy are contrasted with the necessities of climate policy in order to fight climate change. Potential conflicts between the goals of cohesion policy and climate policy are highlighted.
Keywords: F42; F55; Q58; R58; 330; Cohesion policy; Climate policy; Common market; Currency union; Multi-level governance; European Union